Behind Crimmigration: ICE, Law Enforcement, and Resistance in America - Arriaga, Felicia (University of North Carolina Press, 2023)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- List of Illustrations -- Acknowledgments -- Introduction -- Chapter 1. Crimmigration Entities in North Carolina: A 287(g) Program Focus -- Chapter 2. El Hielo anda suelto por esas calles (ICE Is Loose in the Streets): Redefining Local ICE Collaboration -- Chapter 3. The Persistence of 287(g) -- Chapter 4. Collective Amnesia: White Innocence and Ignorance in the Devolution of Immigration Enforcement -- Chapter 5. Melting ICE -- Chapter 6. La migra, la policia, la misma porqueria (Ice, the Police, the Same Crap): Opportunities and Challenges from the 2018 Justice Election -- Conclusion -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z.